Evaluasi Praktikalitas Media Pembelajaran Ekonomi yang Dikembangkan Melalui Video Animasi Berbasis Powtoon - Avicena, Yusuf; Susanti, Dessi; Marsal, Jupri; Fermaisuri, Siti; Friyatmi, Friyatmi (Jurnal Ecogen, 2025)
This research aims to evaluate the practicality of economic learning media by developing PowerPoint-based learning videos as interactive learning media. As an interactive and effective learning media, this learning media is not only visually attractive but must also be practical in its use by teachers and students. The evaluation of the practicality of this learning media includes aspects of convenience for users and in accordance with user needs. The research method for validating the practicality of learning media uses a quantitative descriptive approach using questionnaires and observation instruments given to expert validators, teachers and students at the high school level and above. The results of this research show that Powtoon-based learning media has a high level of practicality as indicated by an average score of 94% in ease of use for teachers and students and 100% in suitability for learning needs. From this research, it is identified that powtoon animation videos are practical and effective learning media in economics learning.